Rule-Based Classification of MMPI Data of Patients with Mental Disorders: Experiments with Basic and Extended Profiles - Jerzy Gomula; Krzysztof Pancerz; Jaroslaw Szkola (International Journal of Computational Intelligence Systems, 2011)
In the research presented in the paper, we test the classification potential for different configurations of the MMPI data used for nosological diagnosis of patients with mental disorders. Originally, each patient is described by an MMPI profile consisting of a set of values of thirteen attributes (the so-called scales). A profile can be extended by different specialized indexes defined in the professional domain literature. Each created index has been proposed by practitioners and has a proper meaning from the clinical point of view. Adding such indexes leads to the extension of the attribute space for cases to be classified. In the paper, we present results of experiments with basic (original) and extended profiles.